Characterization of pathogenic bacterial distribution in extracorporeal membrane oxygenation-related nosocomial infections and the prognostic value of early inflammatory biomarkers for infection survival - Zhao, Zhiwen; Liang, Pengfei; Cai, Lanlan; Zhang, Li; Jia, Qi; Tao, Wentao; Fang, Zhicheng (Frontiers in Microbiology, 2025)
IntroductionExtracorporeal membrane pulmonary oxygenation (ECMO) is the last barrier to save lives and is widely used in the treatment of critical respiratory and circulatory diseases, but infection is one of its common complications. The aim of this study was to analyse the clinical characteristics, survival rates and prognostic factors of patients with ECMO-related nosocomial infections.MethodsThis study retrospectively analysed patients treated with ECMO at a tertiary hospital in China between 2017 and 2023. Patient demographic data, ECMO indications, type of pathogen and site of infection, duration of ECMO and tracheal intubation-assisted breathing, and indicators of inflammation at the time of first infection were collected. Patients were divided into surviving and non-surviving groups based on survival, and differences in early inflammatory markers between the two groups were compared.ResultsA total of 186 patients were treated with ECMO between 2017 and 2023, of whom 61 (32.7%) developed nosocomial infections and 5 declined to participate in the study. In the surviving group after infection, 21 patients (37.5%) had a mean age of 51 years; in the non-surviving group, 35 patients (62.5%) had a mean age of 54 years. The most common site of infection was the respiratory tract (75%), followed by haematogenous infections; the predominant pathogenic organisms were Acinetobacter baumannii (46.43%) and Klebsiella pneumoniae (35.71%). IL-6, hs-CRP, and Plt differed significantly between the two groups (p < 0.05) [IL-6 (40.62 vs. 196.75 μg/mL, p < 0.001), hs-CRP (8.86 vs. 23.60 mg/L, p < 0.001), and Plt (85.00 vs. 48.50 × 109, p = 0.02)], but there were no significant differences in PCT, WBC, and NE. One-way logistic regression analysis showed that IL-6 (OR: 1.02, 95% CI: 1.01–1.03; p = 0.001), hs-CRP (OR: 1.59, 95% CI: 1.02–2.47; p = 0.041), and Plt (OR: 1.01, 95% CI: 1.01–1.02; p = 0.031) were important factors affecting the prognosis of ECMO-related nosocomial infections.ConclusionRespiratory tract infections were the most common during ECMO treatment, and the main pathogen was Acinetobacter baumannii. Early inflammatory markers such as elevated IL-6, hs-CRP and reduced platelet count may be risk factors for poor prognosis and have significance in guiding prognostic assessment.